Fenomenologi Islamisme dan Terorisme - Rosdiawan, Ridwan (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: There are three mainstream theories which elucidate the relationship between Islamic doctrine and political actions that lead to terrorism acts of its believers: Firstly: they who believe that justification of violence and terror acts is inherent products of religious doctrine. Secondly: those who view that terrorism is profane matters, unrelated to religious doctrine whatsoever. Thirdly, opinion that state that terrorism is syncretism as well as interrelative modification between politics and religion. Although the three theories differ in concluding the role of religion in terrorism, they share some analytical approach, which put religion as doctrine and politics as political drive in every terrorism act. To measure the more dominant motive of the two can be done using two perspectives of phenomenology. First perspective views islamist movement as a form of anti modernism which emerges as a cure for western-type of modernization. The west is the enemy. Second perspective concludes that the movement is phenomenon of manifestation as well as response to post-modern development. Islamism emerges as something different, echoing cultural autonomy, alternative political entity as well as moral ideological critique of secularism brought by modernism. Key words: Islamism, terrorism, phenomenology